Why Resilience Matters : The Poverty Impacts of Disasters - Rentschler, Jun E. (World Bank, Washington, DC, 2014)
This paper presents empirical evidence of the profound and long-term damages from adverse natural events on poverty. It analyzes 30 years of macro-level damage data from disasters (including earthquakes, floods, and storms), according to income groups, and shows that low-income countries incur disproportionately large damages relative to their assets. Furthermore, the paper reviews the micro-level evidence of disaster impacts on the livelihoods of the poorest households. The evidence suggests that the poor are significantly more vulnerable and exposed to the economic and human capital losses caused by disasters. It discusses detrimental long-term consequences for the income and welfare of the poor and the presence of poverty traps that result from damages to productive assets, health, and education. The roles of migration and ex-ante behavior are also discussed. In the context of climate change, the paper underscores the importance of considering the detrimental impacts of smaller but repeated crises, for instance caused by changes in local precipitation patterns. Lastly, the paper offers a brief discussion of policy options for strengthening resilience and highlights the need for further research for understanding the complex direct and indirect effects of disasters on the poor.